2019
DOI: 10.1002/slct.201903813
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally Friendly Treatment of Coal‐Bearing Kaolin by Polyhydroxy‐Iron for Anionic Dye Removal

Abstract: Clay material such as kaolin is considered great candidate in industrial water treatment due to its structural properties and abundancy. However, material treatment procedures aimed for adsorption efficiency improvement are generally energy consuming and causes secondary environment contaminations. In the present study, a cost‐effective kaolin modification technique based on polyhydroxy‐iron (PHFe(III)) treatment is applied to coal‐bearing kaolin clay (KC). The modified adsorbent (PHFe(III)/KC) shows a two fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The Langmuir isotherm model was employed for monolayer-based adsorption, where adsorption occurs at identical homogeneous sites within the adsorbent, and the Freundlich model was used to describe multilayer adsorption onto a heterogeneous surface. [17] The fitting parameter values are shown in Table 3. Comparing the R 2 values of the two model fitting equations, it is found that the R 2 of the Freundlich equation is approximately 0.97, which is obviously better than the Langmuir equation fitting results.…”
Section: Chemistryselectmentioning
confidence: 99%
See 1 more Smart Citation
“…The Langmuir isotherm model was employed for monolayer-based adsorption, where adsorption occurs at identical homogeneous sites within the adsorbent, and the Freundlich model was used to describe multilayer adsorption onto a heterogeneous surface. [17] The fitting parameter values are shown in Table 3. Comparing the R 2 values of the two model fitting equations, it is found that the R 2 of the Freundlich equation is approximately 0.97, which is obviously better than the Langmuir equation fitting results.…”
Section: Chemistryselectmentioning
confidence: 99%
“…The results showed that polyhydroxy-iron-modified kaolin has an excellent adsorption efficiency of 75 mg g À 1 , which is significantly higher than that of raw kaolin (12 mg g À 1 ). [17] Fluorine is the most active halogen element located in group VIIA in the second-to-last column of the periodic chart. Fluorine has a high electronegativity and can react with almost all other elements; fluorine is mostly present as an inorganic compound.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, our research group successfully prepared palladium nanoparticle-loaded kaolin and found that it has excellent catalytic activity for the directed C-H functionalization of arylpyrazoles (25). Additionally, in previous work, we successfully prepared polyhydroxy-ironmodified coal-bearing kaolin via an environmentally friendly method for the adsorption removal of anionic dyes from water (26). In this work, we synthesized a series of iron nanoparticle-loaded coal-bearing kaolins and researched the heterogeneous catalytic activity for direct esterification to form C-O bonds via activation of inactive C(sp 3 )-H bonds of cyclic ether by CDC with aryl carboxylic acid.…”
Section: Introductionmentioning
confidence: 99%